SAME-SEX LOVE AS CHALLENGE TO COWBOY’S MASCULINITY PRESENTED IN ANG LEE’S BROKEBACK MOUNTAIN - Kaukab, M. Elfan; Atinia Hidayah (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2021)
Cowboy and his natures have made contribution to the creation of definite masculinity and love relationship between cowboys in Brokeback Mountain affects how cowboy’s masculinity is further depicted. This paper has purpose to reveal how same-sex relationship in the movie challenges the cowboy’s masculinity by analysing the subtitle. This study applied semiotics theory to identify the available data relevant to the construction meaning of cowboy’s masculinity, myth of romantic love and homosexuality. The result shows that homosexual relationships between major cowboy characters in the movie contest the long-established masculinity of cowboy. The struggle to maintain traditional relationship through marriage does not affect social prejudice towards homosexual cowboy.